Synthesis, radiolabeling, and evaluation of 68Ga-labeled aminoquinoxaline derivative as a potent PFKFB3-targeted PET tracer - Chen, Feng; Wu, Yi; Ma, Yixuan; Yin, Honghai; Su, Feijing; Huang, Rui; Wu, Xiaoai; Liu, Qian (Frontiers in Chemistry, 2023)
Glucose provides an abundant supply of energy for tumor cells to sustain their upregulated growth, development, proliferation, and metabolism. Glycolysis, as a multi-step oxidation process, plays important roles in the energy supply for living cells, including malignant tumor cells. Recent studies have revealed that 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 (named PFKFB3), a bifunctional enzyme in glycolysis, is up-regulated in malignant solid tumors and has been regarded as a potential biomarker for the diagnosis and treatment of tumor patients. Based on the structure of selective PFKFB3 inhibitors, we designed and synthesized a radio-metal radiolabeled small molecule, 68Ga-5, which also showed potent selectivity in enzymatic and biochemical tests (with an IC50 value of 12.5 nM). According to further in vitro and in vivo evaluations, 68Ga-5 showed promising properties as a PET ligand, and selective accumulation in PFKFB3-positive tumors was observed in PET images (with max SUV values of 0.60). Our results indicated that radio-metal radiolabeled aminoquinoxaline derivative, as represented by 68Ga-5, held the potential to be developed as selective PFKFB3-targeted PET tracers, and further investigation and optimization would also be required for this scaffold.